The Role of Parents in Implementing the Post-School Transition - Azizah, Nur; Diniarti, Gena; Umar, Veroyunita; Suharmini, Tin (Jurnal Ilmiah Peuradeun, 2024)
The importance of parental involvement in every student's school life has been well-documented in various studies. However, empirical data in the field show that some parents of students with disabilities in Yogyakarta did not fully participate in it. This study aimed to describe the role of parents of students with disabilities in implementing the post-school transition. This study employed qualitative method and used interviews as data collection. The participants in this study were six parents of students with disabilities. This study also revealed that implementation of the transition program post-high school could succeed from parental efforts, namely: 1) the role of students were unique in the implementation transition post-school, 2) the parental role of the students’ need, particularly in the implementation of the transition period post-school, 3) the role of parents students’ need particular in giving training family in implementation of the transition period post school. However, there were a number of possible obstacles to influencing transition program success post-school, namely 1) concern about accompanying child post-school, 2) parents not knowing IEP, 3) parents not being involved in programming, and 4) parents empowerment as companions still less.